MYC oncogene is associated with suppression of tumor immunity and targeting Myc induces tumor cell immunogenicity for therapeutic whole cell vaccination. Issue 3 (23rd March 2021) - Wu, Xiaofang; Nelson, Marie; Basu, Mousumi; Srinivasan, Priya; Lazarski, Christopher; Zhang, Peng; Zheng, Pan; Sandler, Anthony David
Abstract : Background: MYC oncogene is deregulated in 70% of all human cancers and is associated with multiple oncogenic functions including immunosuppression in the tumor microenvironment. The role of MYC in the immune microenvironment of neuroblastoma and melanoma is investigated and the effect of targeting Myc on immunogenicity of cancer cells is evaluated. Methods: Immune cell infiltrates and immunogenic pathway signatures in the context of MYCN amplification were analyzed in human neuroblastoma tumors and in metastatic melanoma. Dose response and cell susceptibility to MYC inhibitors (I-BET726 and JQ1) were determined in mouse cell lines. The influence of downregulating Myc in tumor cells was characterized by immunogenic pathway signatures and functional assays. Myc-suppressed tumor cells were used as whole cell vaccines in preclinical neuroblastoma and melanoma models. Results: Analysis of immune phenotype in human neuroblastoma and melanoma tumors revealed that MYCN or c-MYC amplified tumors respectively are associated with suppressed immune cell infiltrates and functional pathways. Targeting Myc in cancer cells with I-BET726 and JQ1 results in cell cycle arrest and induces cell immunogenicity. Combining vaccination of Myc-inhibited tumor cells with checkpoint inhibition induced robust antitumor immunity and resulted in therapeutic cancer vaccine therapy in mouse neuroblastoma tumors. Despite vigorous antitumor immunity in the mouse melanoma model, upregulation of immunosuppressive pathways enabled tumor escape. Conclusions: This study demonstrates that the Myc oncogene is an appropriate target for inducing tumor cell immunogenicity and suggests that Myc-suppressed whole tumor cells combined with checkpoint therapy could be used for formulating a personalized therapeutic tumor vaccine.